Analysis of Project Based Learning Implementation In Improving the Cognitive Abilities of Children Aged 5–6 Years at TK Roudhoh Serang-Banten - Maulinda, Tasya; Fahmi, Fahmi; Khosiah, Siti (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to analyze the implementation of Project Based Learning (PBL) in improving the cognitive abilities of children aged 5–6 years at TK Roudhoh Serang-Banten. PBL was selected as a learning approach that emphasizes children’s direct experiences in carrying out projects, which is expected to stimulate their cognitive development. This research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The results show that the implementation of PBL at TK Roudhoh was highly effective in enhancing children’s cognitive skills, particularly in critical thinking, creativity, and problem-solving. Teachers acted as facilitators, assisting children in selecting project themes, planning activities, and providing guidance during project implementation. In addition, collaboration among children in completing projects strengthened their social skills and sense of responsibility. Reflection at the end of the project also provided opportunities for children to understand and deepen the material they had learned. Overall, PBL was proven to have a positive impact on developing the cognitive abilities of children aged 5–6 years at TK Roudhoh Serang-Banten.